2011
DOI: 10.1007/s00414-011-0555-8
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine and norbuprenorphine findings in hair during constant maintenance dosage

Abstract: It is still a matter of debate whether a positive correlation between the dose and the amount of drug in the hair exists. Drugs such as buprenorphine (BUP) used under controlled conditions present an opportunity to prove a possible relationship. Due to discrepant findings of BUP/norbuprenorphine (NBUP) ratios in hair, in vitro degradation of both analytes in diluted acid was also investigated. The levels of BUP and NBUP in proximal hair sections from 18 subjects participating in a maintenance program were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
3
9
0
Order By: Relevance
“…Our results are in agreement with previous studies according to which the concentration of NBUP in hair was higher than that of BUP. In all the aforementioned studies, methanolic extraction or alkaline digestion of hair was performed for the isolation of BUP and NBUP. Wilkins et al .…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our results are in agreement with previous studies according to which the concentration of NBUP in hair was higher than that of BUP. In all the aforementioned studies, methanolic extraction or alkaline digestion of hair was performed for the isolation of BUP and NBUP. Wilkins et al .…”
Section: Discussionsupporting
confidence: 94%
“…Our results are in agreement with previous studies [8,21,22] according to which the concentration of NBUP in hair was higher than that of BUP. In all the aforementioned studies, methanolic extraction [21] or alkaline digestion [8,22] of hair was performed for the isolation of BUP and NBUP. Wilkins et al [22] evaluated the levels of BUP and NBUP in human hair, following the administration of multiples doses and found that the highest concentrations of BUP and NBUP were present in hair segments that corresponded to the period of drug treatment.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Degradation of norbuprenorphine is faster than that of buprenorphine, which may serve as a likely explanation for discrepant results of hair analysis reported in the literature. The concentration of both analytes will be underestimated if recovered by acidic procedures (Cone et al 1984;Skopp et al 2011). Lactone-hydroxyl carboxylic acid interconversion presents a challenge in quantitative analysis, which typically occurs for statins (e.g.…”
Section: Influence Of Storagementioning
confidence: 99%